Donor site morbidity of vascularized bone grafts from the medial femoral condyle for osseous revascularization - Struckmann, Victoria; Rusignuolo, Giuseppe; Harhaus-Wähner, Leila; Trinler, Ursula; Bickert, Berthold; Kneser, Ulrich; Kremer, Thomas (Microsurgery, 2020)
Background Vascularized bone grafts from the medial femoral condyle (MFC) are used to gain surgical revascularization of osseous defects. To date objective data regarding the donor site morbidity are limited. This study aims to evaluate the donor site associated outcome after MFC flap harvest. Patients and Methods From 2008 to 2016, 22 patients who underwent MFC bone flap harvest for osseous revascularization of 9 talus, 8 scaphoids, 2 metacarpals, 1 phalanx, 1 pilon tibiale, and 1 distal femur were included. Outcome analysis was performed for the whole cohort as well as for two subgroups (recipient site upper [group A] and lower extremity [group B]) by the lower extremity functional scale (LEFS), the OAK-score of the Swiss Orthopedic Society and the visual analog scale (VAS). Additionally, a 3D gait analysis was performed for four patients. Results The mean flap size was 1 × 1 × 3 cm. No flap loss was observed. One minor surgical revision was performed due to donor site hematoma. Mean follow-up was 35.8 (12-98) months. Mean LEFS-score was 74.9 ± 9.5 (A: 74.3 ± 7.9; B: 75.6 ± 11.2, p > .05) and OAK-score was 92.8 ± 9.4 (A: 93.2 ± 5.8; B: 92.4 ± 12.3, p > .05). At follow-up examination, pain at rest was stated with 0.1 ± 0.2 (A: 0.1 ± 0.3; B 0 ± 0, p > .05) and with activity 0.6 ± 1.4 (A: 1.2 ± 1.8; B: 0 ± 0, p > .05) on VAS. The 3-D gait analysis showed normative walking patterns. Conclusion After MFC flap harvest knee function and gait pattern were almost unimpaired. Donor site morbidity can be considered as being of minor concern in the decision-making for this microvascular procedure.
Gesehen am 25.03.2020